A Wide Survey To Assess Population Of Long-Tailed Macaque Macaca Fascicularis (Primates: Cercopithecidae) In Lowland Region Of South Sumatra - Iqbal, Muhammad; Setiawan, Arum; Pormansyah; Indriati, Winda; Pragustiandi, Guntur; Sevli, Melto; Pratiwi, Putri Rizki; Handayani, Risma; Yustian, Indra (Unmuh Babel Press, 2024)
The Long-tailed Macaque Macaca fascicularis is an Endagered primate because species' population decline very rapidly due to high levels of hunting for trade. A survey to collect data on the M. fascicularis population was carried out in the lowland areas of South Sumatra Province on 7 September-16 October 2023. This survey was carried out in 17 sites in four main districts/cities, including Palembang, Musi Banyuasin, Banyuasin and Ogan Ilir. This survey was recorded 4,316 individuals of M. fascicularis. This number suggest that M. fascicularis has good population number and still commonly found at the survey sites. Based on the survey coverage of the survey area and the total number of ??the lowlands in South Sumatra, we estimate the population of M. fascicularis in the lowlands in this province to be around 300,000 individuals. Further surveys are needed to determine the exact number of M. fascicularis populations in South Sumatra Province.